Immigration, social cohesion and political reaction - Jordan, Bill 1941- (Palgrave pivot, 2021)
This book addresses the challenge for social integration posed by immigration into Western liberal democracies. Movement of people, goods and money across borders has increased in recent decades - the phenomenon known as globalisation. But it has been the migration of refugees from civil wars in the Middle East which has most transformed the political life of European societies, causing the decline in support for the traditional conservative and social democratic parties. It has triggered nationalistic mobilisations and authoritarian regimes, as well as attempts to improved integration in societies. The coronavirus pandemic has added a dimension to these processes, but also opened up new possibilities for transformation. Bill Jordan is Honorary Professor of Social Policy and Social Work at the University of Plymouth, UK. He has authored 30 books on politics, economic and social policy, migration and social work, including Authoritarianism and How to Counter It (2019), Automation and Human Solidarity (2020) and The Age of Disintegration: The Politics and Economics of Division (2020). He held visiting professorships in the Netherlands, Denmark, Germany, Slovakia and the Czech Republic